2008 Eighth International Conference on Hybrid Intelligent Systems 2008
DOI: 10.1109/his.2008.25
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Serendipity in a Content-Based Recommender System

Abstract: Today recommenders are commonly used with various purposes, especially dealing with e-commerce and information filtering tools. Content-based recommenders rely on the concept of similarity between the bought/searched/visited item and all the items stored in a repository. It is a common belief that the user is interested in what issimilar to what she has already bought/searched/visited. We believe that there are some contexts in which this assumption is wrong: it is the case of acquiring unsearched but still us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(83 citation statements)
references
References 9 publications
1
78
0
4
Order By: Relevance
“…The authors use the word serendipity as a concept of surprising and interesting item for the user. The same is stated by Iaquinta et al [17], where they mention serendipity represent items that the users would difficultly find. Moreover, Ge et al [12] define serendipitous items as surprising and pleasant.…”
Section: Serendipitysupporting
confidence: 62%
See 1 more Smart Citation
“…The authors use the word serendipity as a concept of surprising and interesting item for the user. The same is stated by Iaquinta et al [17], where they mention serendipity represent items that the users would difficultly find. Moreover, Ge et al [12] define serendipitous items as surprising and pleasant.…”
Section: Serendipitysupporting
confidence: 62%
“…In a simplified way, a novel item for a user is one that the user has none or little knowledge about [12]. Herlocker et al [14], Iaquinta et al [16,17] state that novelty is when a RS predicts items that the user does not know about and might not discover by other sources. Moreover, novelty has also been defined as how different the recommended item is when compared towards what the user has consumed [36].…”
Section: System Level Noveltymentioning
confidence: 99%
“…The situation is termed as serendipity. Incorporating serendipitous recommendation strategy with reclusive methods alleviate the over specialization problems in recommendation [131]. The authors have suggested hybrid recommendation approach to recommend surprisingly the new items to users.…”
Section: Other Hybrid Recommender Systems Using Reclusive Methodsmentioning
confidence: 99%
“…Besides being relevant to the query, the results must be interesting enough to the user to catch his or her attention, and to encourage further exploration. Although highly subjective, the dimension of interestingness has been used to measure the serendipity of web search results [2] and recommender systems [18]. To make sure we separate intrinsic interestingness of entities from the extent to which a user interested in a search query is interested in a presented result, we ask labelers to consider both questions.…”
Section: User-perceived Qualitymentioning
confidence: 99%